Complementary therapies used in psychoactive substance use disorders in young people: an integrative review - Hernandez Pedroza, Reyna Isabel (2024)
The use of complementary therapies in the care of the population with drug use problems continues to be a phenomenon of interest to the health professional and researcher, especially for nurses, who provide holistic care. Objective: to synthesise the available scientific evidence regarding therapies used in psychoactive substance use disorders in young people. Method: 6-stage integrative review; the databases consulted were Pubmed, Web of science, EBSCO Host, Science Direct, Conricyt and Ovid, using the terms young adult, complementary therapies and substance use disorders, in addition to the Boolean AND and OR. Main results: Twelve articles published predominantly in China, USA and Germany, randomised controlled trial methodology, were selected. Complementary therapies used focused on energy or Qi management, mind-body, breathing and spirituality.  Overall conclusion: the limited evidence on the effects of the use of complementary therapies in substance use disorders results in an urgent need for more research to provide consensus on the beneficial effects of the use of these therapies. It is therefore an area of opportunity for nursing science.